Betty boop and the return of aesthetic functionality: A bitter medicine against 'Mutant Copyrights'? - CALBOLI, Irene (Institutional Knowledge at Singapore Management University, 2014)
This article offers a brief overview of the history and developments of the doctrine of aesthetic functionality in the United States and examines the recent decisions in Fleischer Studios, Inc v AVELA, Inc. In particular, the article argues that the courts in Fleischer added an important element to the interpretation of the doctrine, namely the fact that the courts seemed willing to resort to aesthetic functionality to counter the consequences resulting from the practice of using trade mark protection as an additional form of protection for copyrighted, or once copyrighted, creative works.